Technology development for in-situ measurement of residual stress in arc welded joints of MDN 250 by portable Cosα X-ray diffraction method. (August 2022) - Jose, Bibin; Manoharan, Manikandan; Natarajan, Arivazhagan
Residual stresses are inherent stresses that exist in engineering components even though no external load is applied. They are caused by the non-uniform volumetric shift of the metallic component during manufacturing processes. Welding is a key manufacturing technique that has a substantial impact on the economy since it is required for the production of a diverse variety of products used in the engineering sector. The residual stress primarily affects the stability, durability and performance of the welded joints. Hence its determination is of utmost importance. X-ray diffraction (XRD) is the most commonly used method for residual stress analysis. There are mainly two approaches for measuring residual stress using XRD; one is the sin 2 ψ method and the other is the cosα method. The residual stress measurements using the cosα method are handy, quick and convenient compared to the sin 2 ψ method. This method is well suited for welded joints, as it provides flexibility for testing immediately after the welding operation. Apart from residual stress measurements, the cosα method also gives valuable insights in the form of Debye-Scherrer (DS) rings and full width at half maximum. The present study focuses on the development of a novel technique that not only enables residual stress measurement but also provides a quantitative estimation of hardness and qualitative estimation of grain size without performing metallurgical or mechanical characterization. The material used for the present study is an arc-welded joint of MDN 250 grade maraging steel. The residual stress results show a compressive profile throughout the weldment, with a maximum value of compressive residual stress of 428 MPa at the fusion zone.